2022
DOI: 10.1111/exd.14573
|View full text |Cite
|
Sign up to set email alerts
|

The neuropeptide Substance P facilitates the transition from an inflammatory to proliferation phase‐associated responses in dermal fibroblasts

Abstract: The wound healing process is a product of three successive and overlapping phases of inflammation, proliferation and remodelling. Considerable efforts have been invested in deconstructing the intercellular crosstalk that orchestrates tissue repair, and we investigated the role of neuropeptides released from peripheral neurons upon injury in mediating these interactions. Amongst the most abundant of these neuropeptides secreted by nerves in the skin, is Substance P (SP). Given the role of dermal fibroblasts in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…It was reported that cytokines play a key role in the initiation, severity, and duration of the inflammatory process of the skin [ 15 , 16 ]. In addition, the central involvement of fibroblasts [ 15 ] and keratinocytes [ 16 ] in this process was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that cytokines play a key role in the initiation, severity, and duration of the inflammatory process of the skin [ 15 , 16 ]. In addition, the central involvement of fibroblasts [ 15 ] and keratinocytes [ 16 ] in this process was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that cytokines play a key role in the initiation, severity, and duration of the inflammatory process of the skin [ 15 , 16 ]. In addition, the central involvement of fibroblasts [ 15 ] and keratinocytes [ 16 ] in this process was demonstrated. Therefore, the present study showed for the first time that hydrolyzed collagen inhibited the LPS-induced release of an important and classical panel of pro-inflammatory cytokines (IL-1β, IL-6, IL-8, TNF-α) from human skin fibroblasts (CCD-1072Sk) and human keratinocytes (hKT-nh-skp-KT0026).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation